2007
DOI: 10.1007/s11095-007-9418-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods

Abstract: Supercritical fluid technology for the preparation of puerarin and its phospholipids complex has been proven to have significant advantages over the solvent evaporation technique and other conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…The DSC data of the prepared complex showed a noticeable reduction in the enthalpy as well as the melting point in comparison with catechin and PC. These DSC data are well supported by the results of DSC thermograms of the phospholipid complexes of some phytoconstituents like naringenin, silybin, puerarin, curcumin and gallic acid [12,[15][16][17][18][19]. In all these studies the thermogram of the complex also exhibited a single peak which was different from the peak of phytoconstituents and phospholipids.…”
Section: Dsc Studiessupporting
confidence: 70%
“…The DSC data of the prepared complex showed a noticeable reduction in the enthalpy as well as the melting point in comparison with catechin and PC. These DSC data are well supported by the results of DSC thermograms of the phospholipid complexes of some phytoconstituents like naringenin, silybin, puerarin, curcumin and gallic acid [12,[15][16][17][18][19]. In all these studies the thermogram of the complex also exhibited a single peak which was different from the peak of phytoconstituents and phospholipids.…”
Section: Dsc Studiessupporting
confidence: 70%
“…It is evident that the original peaks of diclofenac and phospholipids disappear from the thermogram of pharmacosomes (complex) and the phase transition temperature is lower than that of phospholipids. The DSC thermograms of the phospholipid complexes of some phytoconstituents, like silybin, puerarin, curcumin and some xanthones, revealed similar results (12)(13)(14).…”
Section: Resultsmentioning
confidence: 75%
“…3). The integrated intensity (the area under the curves of the XRPD patterns) is the characteristics of given sample[22]. It was observed that crystalline diffraction peaks of aceclofenac were disappeared in XRPD of the complex which in turn confirmed the formation of phospholipid complex.…”
Section: Resultsmentioning
confidence: 99%